2019
DOI: 10.1108/oir-03-2018-0093
|View full text |Cite
|
Sign up to set email alerts
|

Social media analytics: analysis and visualisation of news diffusion using NodeXL

Abstract: The purpose of this paper is to provide an overview of NodeXL in the context of news diffusion. Journalists often include a social media dimension in their stories but lack the tools to get digital photos of the virtual crowds about which they write. NodeXL is an easy to use tool for collecting, analysing, visualizing, and reporting on the patterns found in collections of connections in streams of social media. With a network map patterns emerge that highlight key people, groups, divisions and bridges, themes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 39 publications
3
43
0
3
Order By: Relevance
“…The third research objective was to identify whether people really believed 5G and COVID-19 were linked, as Twitter is known to contain humorous content [16]. It was found that 34.8% (n=81/233) of individual tweets contained views that 5G and COVID-19 were linked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third research objective was to identify whether people really believed 5G and COVID-19 were linked, as Twitter is known to contain humorous content [16]. It was found that 34.8% (n=81/233) of individual tweets contained views that 5G and COVID-19 were linked.…”
Section: Discussionmentioning
confidence: 99%
“…The network consists of a total of 10,140 tweets, which are composed of 1938 mentions, 4003 retweets, 759 mentions in retweets, 1110 replies, and 2328 individual tweets. The data was retrieved using NodeXL (Social Media Research Foundation) and the network graph was laid out using the Harel-Koren Fast Multiscale layout algorithm [16]. In interpreting the network graph, the results build upon previous seminal research, which has identified six network shapes and structures that Twitter topics tend to follow [17].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a fundamental feature of SNA is that it examines the structural relationships between socially connected actors (Davies, 2009). SNA offers many insights into social media behaviour, including establishing patterns of situational awareness, alongside insights into the salience of particular messages (Ahmed and Lugovic, 2019); with this in mind, it is possible to examine conversations on twitter not just in terms of their content, but also in their particular patterns of information flow (Isa and Himelboim 2017). Some scholars have viewed social media as the ‘new public square’ and here SNA enables us to map the various constituents of this space and their relations to each other (Smith et al, 2014).…”
Section: Methodological Approaches To Understanding Construction Of Mmentioning
confidence: 99%
“…Some features and tweets of Twitter accounts were found to incline to deliver untrue and unverified intelligence. A few examiners of the situation revealed that the 'humor effect', wherein the users participated in the discussion to mock the treachery involuntarily, was posing a risk for misguidance (Ahmed & Lugovic, 2019). On social media sites misinformation constantly publicized a wrong message among the public, which became a menace for different societies that did something good by adopting protective measures for the safety of their people (Kouzy et al, 2020).…”
Section: Smokescreen Of Media During the Pandemicmentioning
confidence: 99%